Estudo do perfil químico e farmacológico dos venenos de bufonídeos (Amphibia : anura) da Amazônia - Kerkhoff, Jacqueline (2021)
The toxicity of amphibians varies according to the chemical composition of the secretions produced in the glands that animals have on the skin. In bufonids (Anura: Bufonidae), the secreted poison consists of a wide variety of chemical compounds, including bufadienolides, alkaloids, biogenic amines and proteins. These compounds come from the secondary metabolism of animals and several studies have shown pharmacological effects of crude poisons, fractions and isolated molecules. Thus, the objective of this work was (i) to investigate, for the first time, the chemical composition of the secretions of the parotoid glands of the toad Rhinella margaritifera; (ii) to develop a method for the extraction and purification of marinobufagin from Rhinella marina parotoid secretions and (iii) subjecting marinobufagin (MBG) and R. marina (RM) parotoid secretions to in vivo pharmacological models for pain and inflammation. For this, the poisons were collected by manual compression of the glands and, subsequently, dried, pulverized and submitted to extraction in an ultrasonic bath. The animals were returned to nature immediately after collection. For the analysis of the chemical profile, the extract was analyzed by a Liquid Chromatography System with Detection by Ultraviolet Spectroscopy and by Mass Spectrometry (HPLC-DAD-MS), where the mass spectra of the main constituents with the respective ions were obtained molecular (m/z). The MBG isolation used a HPLC-UV semi-preparative system and the molecule was characterized by MS and NMR. For pharmacological tests, male Swiss mice were used, which after receiving pretreatment with RM or MBG and, subsequently, underwent the formalin test and the carrageenan test, to assess the antinociceptive and anti-inflammatory activities, respectively. A total of 18 compounds were identified in the extract of R. margaritifera, with bufotalina being the major compound. As for the isolation of MBG, it was possible to obtain the molecule in sufficient quantity and high purity content, with yield and purity obtained, respectively, 20% and 96%. The results of the pharmacological tests of RM and MBG demonstrated antinociceptive and anti-inflammatory activity, and suggest that the extract and bufadienolide have therapeutic potential for the treatment of pain and inflammation. All of these results contribute to the knowledge of the Amazonian anurofauna, as well as to support new studies.